The Higher the Score, the Darker the Core: The Nonlinear Association Between Grandiose and Vulnerable Narcissism - Jauk, Emanuel; Kaufman, Scott Barry (Frontiers in Psychology, 2018)
Narcissism is a truly Janusian phenomenon, consisting of both narcissistic grandiosity, exhibitionism, admiration-seeking, boldness, and dominance on the one hand, and narcissistic vulnerability, introversion, withdrawal, hypersensitivity, and anxiety on the other hand. While there is broad consensus that these two seemingly contradictory faces of narcissism can be empirically discerned and have different implications for psychological functioning and mental health, there is not yet agreement on whether grandiose and vulnerable narcissism should be regarded as independent traits, or as two manifestations of one personality trait. Previous research indicates that both views hold true when the level of grandiosity is considered a moderating factor: while grandiose and vulnerable narcissism are largely unrelated in the range of normal personality variation, they are correlated in the range of high grandiosity (Jauk et al., 2017b). Here, we replicate and extend this work in an independent sample (N = 891) using a more comprehensive narcissism inventory grounded in a new trifurcated model of narcissism. The trifurcated model partitions narcissism into three main personality dimensions: agentic extraversion, antagonism, and neuroticism. We found a significant breakpoint in the association between narcissistic grandiosity and vulnerability at 75% cumulative frequency of grandiosity. While grandiosity and vulnerability are unrelated below this breakpoint (r = .02), they are strongly correlated above (r = .45). In the lower range of grandiose narcissism, grandiosity draws more upon agentic extraversion and is largely associated with mental health. In the upper range, however, grandiosity is more strongly linked to antagonism, and is substantially associated with fear, negative affect, and depression. These findings provide evidence for the view that grandiose and vulnerable narcissism are distinct traits at lower levels of grandiosity, but blend into an antagonistic core with signs of psychological maladjustment at higher levels. Implications for research on narcissism as a personality trait, as well as clinical practice, are discussed.